2017
DOI: 10.1590/1981-863720170002000063275
|View full text |Cite
|
Sign up to set email alerts
|

Cephalometric analysis: concordance between software

Abstract: ConclusionThe software can be interchangeably applied in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
1
0
0
Order By: Relevance
“…The upper incisor to A-Pog (linear) again showed a statistically significant difference between the mean values obtained using the software. A similar difference for Nasion - Point A (Linear) was reported by Correia et al [ 20 ] On the contrary, Tikku et al [ 21 ] in their study comparing NemoCeph with manual also noted a statistically significant difference for L1-NB, but was comparable clinically.…”
Section: Discussionsupporting
confidence: 79%
“…The upper incisor to A-Pog (linear) again showed a statistically significant difference between the mean values obtained using the software. A similar difference for Nasion - Point A (Linear) was reported by Correia et al [ 20 ] On the contrary, Tikku et al [ 21 ] in their study comparing NemoCeph with manual also noted a statistically significant difference for L1-NB, but was comparable clinically.…”
Section: Discussionsupporting
confidence: 79%
“…[2,3] The popularly used digital tracing Software's include Dolphin Imaging, Vistadent, Nemoceph, and Quick Ceph. [4] It was found that there are no significant differences between the manual and computer-assisted cephalometric analysis except in one or two parameters [4][5][6][7] In recent years smartphone apps have taken up the role of computer software in performing cephalometric analysis. Smartphone applications are portable and available free of cost.…”
Section: Introductionmentioning
confidence: 99%